2020
DOI: 10.3390/ijms21072418
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Regulation of miR-124-3p in the Perilesional Cortex after Experimental and Human TBI

Abstract: Traumatic brain injury (TBI) dysregulates microRNAs, which are the master regulators of gene expression. Here we investigated the changes in a brain-enriched miR-124-3p, which is known to associate with major post-injury pathologies, such as neuroinflammation. RT-qPCR of the rat tissue sampled at 7 d and 3 months in the perilesional cortex adjacent to the necrotic lesion core (aPeCx) revealed downregulation of miR-124-3p at 7 d (fold-change (FC) 0.13, p < 0.05 compared with control) and 3 months (FC 0.40, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 104 publications
(139 reference statements)
0
22
0
Order By: Relevance
“…For example, canonical STaT3 signaling is associated with JaK-STaT signaling, whereby STaT3 is phosphorylated on tyrosine 750 (Y750), facilitating STaT3 homodimerization, nuclear translation, dna binding and initiation of transcription (42) activity in various cells. certain studies have reported the axis of mir-124-3p/STaT3 (47)(48)(49), but to the best of our knowledge, no previous study has focused on the functions of STaT3 in ec proliferation. inhibition of the STaT3 signaling pathway impairs angiogenesis and perfusion recovery in the muscles of patients with Pad (50).…”
Section: Discussionmentioning
confidence: 99%
“…For example, canonical STaT3 signaling is associated with JaK-STaT signaling, whereby STaT3 is phosphorylated on tyrosine 750 (Y750), facilitating STaT3 homodimerization, nuclear translation, dna binding and initiation of transcription (42) activity in various cells. certain studies have reported the axis of mir-124-3p/STaT3 (47)(48)(49), but to the best of our knowledge, no previous study has focused on the functions of STaT3 in ec proliferation. inhibition of the STaT3 signaling pathway impairs angiogenesis and perfusion recovery in the muscles of patients with Pad (50).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 88 records were then manually screened and assessed for eligibility against the selection criteria previously described ( Section 2.2 ). Seventy-eight results were excluded during this process, leaving 10 miRNA studies for inclusion in the systematic review [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Figure 1 provides an overview of the miRNA literature search and study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…The injury model, time point of analysis post-TBI and analysis method differed across the studies. Supplementary Materials Tables S1 and S2 provide an overview of the study characteristics for the included papers [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. The data collected here allowed us to establish whether performance of a meta-analysis was possible.…”
Section: Resultsmentioning
confidence: 99%
“…11 Hybridization was performed using a 5 nM double-digoxigenin (DIG) (3 0 and 5 0 )-LNA probe for a 134-inhibitor probe (Exiqon) or an LNA-DIG scramble inhibitor probe. The cellular uptake mean ratio was calculated as per the formula described by Vuokila et al 47 for each region of interest (ROI). Sections for immunohistochemistry were incubated with primary antibody (NeuN, GFAP, Iba-1, or parvalbumin; all from Cell Signaling Technology) and fluorescently labeled secondary antibodies (Alexa Fluor 488 or 546).…”
Section: Reactome Pathway Enrichment Analysismentioning
confidence: 99%